Penggunaan Dana Desa Tahun 2020 di Desa Hungayonaa dalam Sistem Penyampaian Laporan - Fransmulya Herman; Syarwani Canon; Melizubaida Mahmud (Universitas Negeri Gorontalo, 2021)
This study aimed to find out the Management of Village Funds in Hungayonaa Village,Tilamuta District, Boalemo Regency in 2020 and the influence factors. It employed aQualitative Research Methods by parsing the data descriptively. Data collection techniqueswere carried out by observation, interviews, and documentation through qualitativedescriptive analysis techniques. The results showed that the management of the Village Fund including Planning, Implementation, Administration, Reporting and Accountability, has been following the Regulation of the Minister of Home Affairs Number 113 of 2014concerning Village Financial Management. Further, factors that influence the management of Village Funds were supporting and inhibiting factors. Supporting factors were community participation, facilities, and infrastructure, while the inhibiting factor was Human Resources.